Synthesis and Molecular Docking Study of 1-(3-Chloropropyl)-3,5-Bis((E)-4-Methoxybenzylidene)Piperidin-4-One as Dengue Virus Type 2 (DEN2) NS2B/NS3 Protease Inhibitor Candidate - Romi Habibi; Noval Herfindo; Rudi Hendra; Hilwan Y. Teruna; Adel Zamri (Pharmacology and Clinical Pharmacy Research)
Curcumin is a secondary metabolite compound that has diverse biological activities. However, it is easily hydrolyzed at physiological pH due to the presence of the β-diketone group. Therefore, the replacement of the β-diketone group with mono ketone is expected to overcome this issue. We hereby report the synthesis of mono ketone curcumin derivatives from piperidone by two-steps reactions. The synthesis of curcumin derivate 3 was carried out by Claisen-Schmidt condensation between 4-piperidone and 4-methoxybenzaldehyde using alkaline catalyst. The synthesized curcumin derivate 3 was then reacted with the 1-bromo-3-chloropropane to produce curcumin derivate 5, 1-(3-chloropropyl)-3.5-bis((E)-4-methoxybenzylidene)piperidin-4-one, with 72% yield. The calculated docking scores, the curcumin derivate 5 possessed a better affinity for receptors than the standard panduratin A. The curcumin derivate 5 has a lower docking score of -6.40 kcal/mol compared to panduratin A with value of -5.18 kcal/mol and also had strong binding interactions to DEN2 NS2B/NS3 protease. Thus, this compound is promising candidate as a new anti-dengue agent.